Responses of postreceptoral pathways elicited by L- And M-cone isolating ON- And OFF-electroretinograms in glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. To compare the electroretinographical (ERG) responses elicited by L- and M-cone isolating ON- and OFF-sawtooth stimuli in normal subjects and glaucoma patients. METHODS. Twenty-one normal subjects and 44 primary open-angle glaucoma patients participated in the study. L- and M-cone isolating (18% cone contrast; 284 cd/m2) rapid ON- and rapid OFF-sawtooth (4 Hz) stimuli with two stimulus sizes (full-field (FF) and central 70° diameter) were generated using the triple silent substitution technique. ON- and OFF-response asymmetries were studied by adding the two (to obtain L-add and M-add responses). The initial positive (P) and subsequent late negative (LN) components of the L-add and M-add ERGs were compared between the subject groups and correlated with retinal nerve fiber layer thickness (RNFLT) and pattern ERG responses. RESULTS. The responses to L-ON and to M-OFF stimuli and vice versa resembled each other particularly with 70° stimuli. The PL-add amplitudes were not significantly different between the normal subjects and glaucoma patients, whereas the LNL-add amplitude was significantly (P < 0.01) smaller in the glaucoma patients. Both PM-add and LNM-add were not significantly different between the subject groups. The PERG amplitude with 0.8° check sizes and the 0.8°/16° amplitude ratio (PERG ratio) were significantly (P < 0.05) different between the subject groups. The 70° LNL-add amplitude and the 0.8° PERG amplitude were significantly correlated with RNFLT. CONCLUSIONS. The ERGs to 70° cone isolating sawtooth stimuli reflect cone opponency. The cone opponent ERG responses were not significantly different between glaucoma patients and normal subjects. Luminance driven L-add responses were significantly different, indicating that central luminance signals are mainly affected in glaucoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Glaucoma; Magnocellular; ON- and OFF electroretinogram; Parvocellular; Sawtooth stimuli; Silent substitution; Stimulus size